Hippocampal NLRP1 inflammasome mediates anxiety-like behavior in mice with hypothyroidism - Yu-Wei Cheng; Zhi-Hui Zou; Chen-Lu Lou; Ming-Rui Tong; Jin-Kai Li; Wen-Hui Zhu; Yu-Lin Lu; De-Fa Zhu; Qi Xu; Yong-Xia Xu (Scientific Reports)
Abstract Hypothyroidism is associated with anxiety and depression. However, the mechanisms underlying these neuropsychiatric symptoms remain largely unknown. This study aimed to investigate the role of the NLRP1 inflammasome in anxiety-like behavior in mice with hypothyroidism. Male C57BL/6j mice were divided into three groups: euthyroid controls, a hypothyroid model group induced by propylthiouracil, and a hypothyroid group treated with levothyroxine (L-T4). Anxiety-like behavior was assessed using both the open field test and the elevated plus maze. Protein levels of NLRP1 inflammasome components and associated cytokines in the hippocampus were examined by Western blot analysis. Mice with hypothyroidism exhibited anxiety-like behavior, as evidenced by decreased activity in the central area of the open field and reduced time spent in the open arms of the elevated plus maze. These behavioral changes were accompanied by an increased expression of NLRP1 inflammasome components (NLRP1, ASC, and Caspase-1) and associated cytokines (IL-1β, IL-18, and IL-6) in the hippocampus. L-T4 treatment reversed both the behavioral deficits and inflammatory changes. Our findings highlight the crucial role of NLRP1 inflammasome activation in the hippocampus in mediating anxiety-like behavior in hypothyroid mice, shedding light on the mechanisms underlying hypothyroidism-related psychiatric comorbidities and identifying potential therapeutic targets.